2020
DOI: 10.3324/haematol.2020.254045
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic recovery and immune reconstitution after axicabtagene ciloleucel in patients with large B-cell lymphoma

Abstract: Chimeric antigen receptor (CAR) T-cell therapy targeting CD19 may be associated with long-term adverse effects such as cytopenia and immune deficiency. In order to characterize these late events, we analyzed 31 patients with relapsed or refractory large B-cell lymphoma treated with axicabtagene ciloleucel at our institution on two clinical trials, ZUMA-1 (clinicaltrials gov. Identifier: NCT02348216) and ZUMA-9 (clinicaltrials gov. Identifier: NCT03153462). Complete blood counts, lymphocyte subsets, and immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 26 publications
3
121
1
2
Order By: Relevance
“…Prolonged cytopenia is a common finding in CD19 -targeting CART therapy 2 , 3 with up to 29% and 42% of 31 lymphoma patients experiencing grade 3-4 neutropenia and thrombocytopenia after axicabtagene ciloleucel, 4 which is consistent with data from the pivotal ZUMA-1 (17% ≥3 cytopenias at 3 mo) 5 and JULIET (24% ≥3 cytopenias at 28 d) 6 trials. In our own cohort of patients treated with commercially available CD19 -directed chimeric antigen receptor (CAR) T-cells, 9/35 patients (26%) experienced prolonged neutropenia.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Prolonged cytopenia is a common finding in CD19 -targeting CART therapy 2 , 3 with up to 29% and 42% of 31 lymphoma patients experiencing grade 3-4 neutropenia and thrombocytopenia after axicabtagene ciloleucel, 4 which is consistent with data from the pivotal ZUMA-1 (17% ≥3 cytopenias at 3 mo) 5 and JULIET (24% ≥3 cytopenias at 28 d) 6 trials. In our own cohort of patients treated with commercially available CD19 -directed chimeric antigen receptor (CAR) T-cells, 9/35 patients (26%) experienced prolonged neutropenia.…”
supporting
confidence: 65%
“…The underlying mechanisms remain poorly understood. Higher grade CRS with or without neurotoxicity 2 , 4 , 7 consistently correlated with prolonged cytopenias. In a cohort of 41 patients suffering from lymphoma, leukemia, and myeloma, correlation of CRS and high inflammatory parameters still remained significant after adjustment for other factors that cause prolonged cytopenia (ie, baseline cytopenia, CAR construct).…”
mentioning
confidence: 88%
“…It has been shown that cytopenias developing after CAR-T cell therapy may last for a long time, exceeding 30 days (10,13,15,138,139). This phenomenon is termed as prolonged hematologic toxicity (PHT), and it is characterized with ≥ grade 3 neutropenia or thrombocytopenia following CAR-T cells infusion(exceeding 30 days) (15).…”
Section: Cytopeniasmentioning
confidence: 99%
“…Currently approved CAR T-cell therapies target antigens found on B-cells such as CD19, resulting in B-cell aplasia and hypogammaglobulinemia that can last from months to years [48].…”
Section: Infectionmentioning
confidence: 99%